Mangosteen Peel Extract (Garcinia mangostana L.) as a Potential Complementary of Leukemia Therapy: In Vitro and In Silico Studies - Gondokesumo, Marisca Evalina; Novilla, Arina; Prahastuti, Sijani; Zahiroh, Fadhilah Haifa; Kusuma, Hanna Sari Widya; Widowati, Wahyu; Azis, Rizal; Hadiprasetyo, Dhanar Septyawan; Nurjamil, Aris Muhammad; Surakusumah, Wahyu; Adha, Khoerotul Nur Fadhilah (Journal of Mathematical and Fundamental Sciences, 2025)
Leukemia is caused by abnormal white blood cell proliferation that leads to disruption of conventional blood cell functions. Mangosteen (Garcinia mangostana L.) contains phytochemical compounds with strong anticancer properties, according to various cancer studies. This study investigated the potential of mangosteen peel extract (MPE) as an anti-leukemia agent through molecular docking of LC-MS-identified compounds against FLT-1 and AKT proteins, followed by in vitro evaluation on HL-60 cells, namely cytotoxic (WST-8 assay), ROS levels and senescence (flow cytometry), and then FLT1 and AKT gene expression (qRT-PCR). LC-MS identified α-mangostin, β-mangostin, γ-mangostin, mangostinone, and epicatechin as the main compounds. Molecular docking revealed strong binding affinities from −8.5 to −9.9 kcal/mol against AKT, and from −9.0 to −9.9 kcal/mol against FLT-1. MPE (500 µg/mL) decreased cell viability and increased inhibition of HL-60 cells. Intracellular ROS levels decreased significantly at 0.6, 1.2, and 2.4 µg/mL MPE. MPE induced cell senescence especially at 1.2 and 2.4 µg/mL. Gene expression analysis revealed downregulation of AKT at 1.2 and 2.4 µg/mL and FLT1 at 2.4 µg/mL. These findings suggest that MPE may exert multifactorial anti-leukemic mechanisms, including apoptosis, ROS modulation, senescence induction, and regulation of AKT and FLT1 expression.